Analisis Kesediaan Membayar (Willingness to Pay) Konsumen Terhadap Sayuran Organik di Pasar Modern Kabupaten Bandung Barat - Zahran, Muhammad Hafidz; Santoso, Siswanto Imam; Nurfadillah, Suryani (Universitas Galuh, 2025)
The increasing demand for organic products is driven by concerns related to health issues. This study aimed to describe consumer characteristics, calculate the average maximum Willingness to Pay (WTP), and analyze the factors influencing consumer WTP for organic vegetables in West Bandung Regency. The research was conducted from December 2024 to January 2025 in five modern markets in West Bandung Regency. The method used was a survey method. Respondents were selected through accidental and quota sampling. The sample size was determined using the Lemeshow formula, resulting in 100 respondents. The data analysis methods included descriptive analysis, the Contingent Valuation Method (CVM), and multiple linear regression analysis. The results showed that organic vegetable consumers were mostly female, aged 31–40 years, held a bachelor's degree (Strata 1), worked as civil servants, military, or police personnel (PNS/TNI/POLRI), had a monthly income ranging from Rp3,000,000 to Rp5,999,999, and typically purchased organic vegetables at prices ranging from Rp10,000 to Rp12,999. Consumers also gave high ratings for product quality and the health benefits of organic vegetable consumption. The average maximum WTP for organic broccoli was 10.84% above the original price, for lettuce 9.09%, for water spinach (kangkung) 8.75%, for spinach 8.53%, for mustard greens (sawi) 9.45%, and for pakcoy 7.5%. Factors such as age, education level, occupation, income level, product price, product quality, and health benefits simultaneously influenced consumers’ willingness to pay for organic vegetables. Partially, the variables of age, education level, product price, product quality, and health impact had a significant effect on WTP.